Comparison of sprinting mechanics of the double transtibial amputee oscar pistorius with able bodied athletes - Potthast, W.; Brueggemann, G. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The purpose of this study was to examine the overall kinetics and the kinetics at the joints of the lower limb while sprinting at maximum speed, and to compare the data of a double transtibial amputee (OP) and able-bodied controls running at the same level of performance. One double transtibial amputee, and five able-bodied sprinters participated in the study. The athletes performed submaximal and maximal sprints on an indoor track embedded with 4 Kistler force plates while recorded with a 12 camera Vicon 624 system. OP displayed lower mechanical work (stance phase), external joint moments and joint power at the hip and the knee joints while displaying higher values of joint power at the (prosthetic) ankle joint compared to able-bodied athletes. The mechanical work at the knee joints was 11 times higher in the negative phase and 8.1 times higher in the positive phase during stance in the able-bodied athletes compared to OP.